Epichloë Endophyte-Promoted Seed Pathogen Increases Host Grass Resistance Against Insect Herbivory - Laihonen, Miika; Saikkonen, Kari; Helander, Marjo; Vázquez de Aldana, Beatriz R.; Zabalgogeazcoa, Iñigo; Fuchs, Benjamin (Frontiers in Microbiology, 2022)
Plants host taxonomically and functionally complex communities of microbes. However, ecological studies on plant–microbe interactions rarely address the role of multiple co-occurring plant-associated microbes. Here, we contend that plant-associated microbes interact with each other and can have joint consequences for higher trophic levels. In this study we recorded the occurrence of the plant seed pathogenic fungus Claviceps purpurea and aphids (Sitobion sp.) on an established field experiment with red fescue (Festuca rubra) plants symbiotic to a seed transmitted endophytic fungus Epichloë festucae (E+) or non-symbiotic (E−). Both fungi are known to produce animal-toxic alkaloids. The study was conducted in a semi-natural setting, where E+ and E− plants from different origins (Spain and Northern Finland) were planted in a randomized design in a fenced common garden at Kevo Subarctic Research Station in Northern Finland. The results reveal that 45 % of E+ plants were infected with Claviceps compared to 31 % of E- plants. Uninfected plants had 4.5 times more aphids than Claviceps infected plants. By contrast, aphid infestation was unaffected by Epichloë symbiosis. Claviceps alkaloid concentrations correlated with a decrease in aphid numbers, which indicates their insect deterring features. These results show that plant mutualistic fungi can increase the infection probability of a pathogenic fungus, which then becomes beneficial to the plant by controlling herbivorous insects. Our study highlights the complexity and context dependency of species–species and multi-trophic interactions, thus challenging the labeling of species as plant mutualists or pathogens.